Peluang Ekonomi Manfaat Tanaman Gadung di Desa Jetiskidul Kecamatan Arjosari Kabupaten Pacitan - Prasetya, Afendi Dwi; Anantyasari, Malta (Al-DYAS, 2023)
Gadung (Dioscoreahispida Dennst), is a tuber-like plant that grows vines and also climbs with a height of 5-20 m. tuber production from gadung plants can be increased if this plant is cultivated intensively because naturally this plant can grow and develop very well in tropical climates. Gadung tubers have various health benefits and have high economic value. Processed gadung tubers, commonly known as gadung crackers, can become a business opportunity to meet the needs of the community, both from the upper, middle and lower classes. Because these processed products are light and healthy snacks and the price is affordable. This study uses a qualitative approach. The type of research used is library research with the documentation method, namely finding and studying data regarding variables in the form of notes, documents, books, journals and so on. The data sources used are primary and secondary data sources. The data analysis technique used is content analysis method. To test the validity of this research data using a credibility test by increasing persistence, researchers also use source triangulation techniques. Business opportunities in doing business have many indicators that must be recognized and several factors that must be considered so that they can minimize the impact of failure of business opportunities in their business